1986
DOI: 10.1021/jm00157a010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-(4-substituted-1-piperazinyl)benzimidazoles as H1-antihistaminic agents

Abstract: A series of 2-(4-substituted-1-(homo)piperazinyl)benzimidazoles was prepared and tested for H1-antihistaminic activity in vitro and in vivo. Most of the compounds showed antihistaminic activity and some of the 1-[2-(substituted-oxy)ethyl] derivatives exhibited potent activity. In a structure-activity comparison it was found that the oxygen atom in the 2-(substituted-oxy)ethyl group at the 1-position of the benzimidazole nucleus played an important role for potent antihistaminic activity, especially in vivo. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 1 publication
(2 reference statements)
1
47
0
Order By: Relevance
“…Treatment of compound 10 with 1/3 equivalents of triphosgene under basic conditions 9 resulted in formation of benzimidazolone 11, which was in turn converted to compound 12 by the action of POCl 3 . 10 Finally when compound 12 was reacted with two equivalents of compound 6 to obtain compound 3 according to literature reports on similar reactions, 3,4 compound 4 was the only product isolated while substantial amount of compound 12 was recovered. Although synthesis of compound 3 requires one equivalent each of compound 6 and compound 12, excess of compound 6 was used to trap the released HCl.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of compound 10 with 1/3 equivalents of triphosgene under basic conditions 9 resulted in formation of benzimidazolone 11, which was in turn converted to compound 12 by the action of POCl 3 . 10 Finally when compound 12 was reacted with two equivalents of compound 6 to obtain compound 3 according to literature reports on similar reactions, 3,4 compound 4 was the only product isolated while substantial amount of compound 12 was recovered. Although synthesis of compound 3 requires one equivalent each of compound 6 and compound 12, excess of compound 6 was used to trap the released HCl.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Even though Moraxella catharralis has not been identified as an important human pathogen, it is obvious that it has a significant financial impact on global health care systems. [3] Benzimidazoles displayed a variety of biological effects, such as antihelmintic, [4] antiviral, [5,6] anticancer, [7] anti-inflammatory [8] or antioxidant [9] activities. Consequently, benzimidazole core received attention as an important pharmacophore for the development of novel B antimicrobial agents in inhibiting synthesis of microbial nucleic acids and proteins and preventing the growth of various microorganisms ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The different benzimidazole derivatives are associated with a wide range of biological activities such as anti-cancer [13] , anti-viral [21] , anti-bacterial [7,9,22] , anti-fungal [18] , anti-helmintic [23] , antiinflammatory [10] , anti-histaminic [15] , proton pump inhibitor [8] , anti-oxidant [2] , anti-hypertensive [14] and anti-coagulant [17] properties. Literature review shows that along with the benzimidazole derivatives, 2-substituted ones are found to be pharmacologically more important and hence syntheses of 2-substituted benzimidazoles are the reasonable area of research [4,19] .…”
Section: Introductionmentioning
confidence: 99%